2008
DOI: 10.1002/gps.2133
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, functional and behavioral factors associated with the burden of caring for geriatric patients with cognitive impairment or depression: evidence from a South American sample

Abstract: These findings suggest that behavioral symptoms are an important factor associated with caregiver burden in patients with cognitive impairment, dementia, or depression, while functional and cognitive factors seem to also have an influence in patients with cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 11 publications
3
26
1
1
Order By: Relevance
“…Problematic behaviour of care recipients, such as verbal abuse and difficulty in sleeping, were also predictors of a greater burden, possibly by creating physical and emotional difficulties for the caregiver. This finding is supported by those of other studies (24,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 91%
“…Problematic behaviour of care recipients, such as verbal abuse and difficulty in sleeping, were also predictors of a greater burden, possibly by creating physical and emotional difficulties for the caregiver. This finding is supported by those of other studies (24,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 91%
“…Factors related to the successful group Our longitudinal study showed that the prevalence of dementia among the elderly was higher and that behavioural disturbances were more severe in the unsuccessful group, which is consistent with many other cross-sectional studies that have shown a positive relationship between the burden or depressive symptoms of the caregiver and the behavioural disturbances associated with dementia [7,11,[27][28][29][30][31]. In addition, caregivers spent a significantly longer time caregiving and attending the elderly in the unsuccessful group, which is also consistent with previous findings [7,[10][11][12][13].…”
Section: Discussionsupporting
confidence: 90%
“…Caregiving is a multidimensional concept [3] , with an impact on both physical and mental health, as well as on family finances and their structure of time. All these impacts have been shown to negatively affect the caregivers of patients with dementia [4][5][6] , in some cases, more than in the caregivers of non-demented patients [7] .Health-related quality of life (HRQoL) is an important indicator of health. The HRQoL combines the presence…”
mentioning
confidence: 99%